Penilaian Kelas Kemampuan Lahan Sebagai Dasar Rekomendasi Konservasi Tanah di Desa Merdeka Kabupaten Karo - Pasaribu, Parlin Hotmartua Putra (Inovasi, 2025)
Land capability class assessment is important to determine land characteristics as a basis for land management to minimise land damage. This research aims to determine the land capability class as a direction for soil conservation. The data analysis used to classify the land capability class is the Scorring method. The results showed that the land capability in Merdeka Village was generally good. This is because the land in Merdeka Village has high land parameters and small land class boundaries so that it can be utilised with intensive land cultivation. The main indicator in determining land class is slope/topography. Merdeka Village has 4 (four) land capability classes. Class I (AIUc, AIIUc, AIBu) can be managed very intensively with the application of vegetative and chemical conservation. Class II (AIIIUc, AIVUc, AIIBu, and AIISs) is managed with limited intensive with the application of vegetative and mechanical conservation. Class III (AVUc, AIVBu, AIIIHz, AIIHz) is managed on a limited basis with intensive application of mechanical and vegetative conservation. Class IV (AIVHz, AVHz) is managed under a grazing system with vegetative conservation. Mechanical soil conservation is in the form of planting in the direction of contour lines, terracing, and drainage. Vegetative soil conservation in the form of crop rotation, use of mulch, ground cover plants, and enrichment of forestry plants. Chemical conservation in the form of fertilisation/ liming. The conservation measures taken on land units in each land capability class tend to be different, this is mainly influenced by different slopes and land use. With soil conservation, it will provide relatively maximum results in sustainable land management efforts. As for land conservation efforts, it needs the role of various stakeholders, especially the local government in planning, monitoring and evaluation, and further research. Keywords: Land Capability Class, Scoring Method, Soil Conservation.